Human saliva can be a diagnostic tool for Zika virus detection. Issue 5 (September 2019) - Khurshid, Zohaib; Zafar, Muhammad; Khan, Erum; Mali, Maria; Latif, Muhammad
Abstract: Zika virus (ZIKV), an Aedes mosquito-borne flavivirus, has captured public health attention worldwide. Initially, the virus was reported in Africa and Asia. However, the outbreak of ZIKV in Brazil and the United States of America demonstrated the global health risk. Symptoms of ZIKV infection vary from mild fever, rash, and joint pain to an apparent increase in microcephaly in infants and severe manifestations including Guillain–Barré syndrome in adults. Such consequences led to enormous health challenges, and consequently the World Health Organization declared a global health emergency. This review incorporates all aspects of ZIKV that could significantly impact human health, including epidemiology, clinical presentation, possible complications, cutting-edge therapeutic management of ZIKV infection, and latest developments in ZIKV diagnosis, particularly the value of human saliva as a diagnostic fluid.